Embryonic and larval neural connectivity: progressive changes in synapse form and function at the neuromuscular junction mediated by cytoskeletal regulation. (15th March 2013) - Long, Jennifer B.; Van Vactor, David
Abstract During development, precise formation of millions of synaptic connections is critical for the formation of a functional nervous system. Synaptogenesis is a complex multistep process in which axons follow gradients of secreted and cell surface guidance cues to reach their target area, at which point they must accurately distinguish their specific target. Upon target recognition, the axonal growth cone undergoes rapid growth and morphological changes, ultimately forming a functional synapse that continues to remodel during activity‐dependent plasticity. Significant evidence suggests that the underlying actin and microtubule (MT) cytoskeletons are key effectors throughout synaptogenesis downstream of numerous receptors and signaling pathways. An increasing number of cytoskeletal‐associated proteins have been shown to influence actin and MT stability and dynamics and many of these regulators have been implicated during synaptic morphogenesis using both mammalian and invertebrate model systems. In this review, we present an overview of the role cytoskeletal regulators play during the formation of the Drosophila neuromuscular junction. WIREs Dev Biol 2013, 2:747–765. doi: 10.1002/wdev.114 The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.